A lithium-doped material, preparation method and application thereof

Through the preparation method of lithium-doped materials, chemical adsorption is used to achieve separation of nitrogen and methane, which solves the problem of unsatisfactory nitrogen/methane separation effect in the prior art, achieves efficient and low-cost separation effect, and ensures the material Recyclable.

CN118874439BActive Publication Date: 2024-12-20QILU INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411365803.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The prior art has poor effect in the separation of nitrogen and methane, and is costly, making it difficult to achieve efficient separation.

Method used

Using a preparation method of lithium doped material, including Polymer 1 synthesis, Naphthyl lithium preparation and Li@Polymer 1 preparation steps, the separation of nitrogen and methane is achieved by chemical adsorption of nitrogen. The material has no adsorption ability to methane, and nitrogen adsorption is Reversible, high temperature release.

Benefits of technology

It realizes efficient separation of nitrogen and methane, the material preparation method is simple, low cost, and the material can be recycled, suitable for the separation of nitrogen/methane and CO2/N2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118874439B_ABST
    Figure CN118874439B_ABST
Patent Text Reader

Abstract

The present invention discloses a lithium-doped material, a preparation method and application thereof, and belongs to the technical field of lithium-doped materials. The technical scheme includes a Polymer 1 synthesis step, a naphthyl lithium preparation step, and a Li@Polymer 1 preparation step; the Li@Polymer 1 preparation step includes: mixing and stirring the dried Polymer 1 and the tetrahydrofuran solution of naphthyl lithium in a glove box, fully reacting, and draining the solvent under high vacuum conditions to obtain a solid powder of the lithium-doped material. The present invention is applied to nitrogen / methane separation, solves the problem that the existing nitrogen / methane separation effect is not ideal, has the characteristics of simple preparation method, low cost, and the synthesized material can effectively realize the separation of nitrogen and methane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-doped materials, and in particular relates to a lithium-doped material, a preparation method and application thereof. Background Art

[0002] Methane, the main component of natural gas, has an energy density of only 64% of gasoline, but due to its abundant reserves, the highest carbon-to-hydrogen ratio, and low carbon dioxide emissions after combustion, it has become an ideal clean energy source that is expected to replace fossil fuels. However, low-quality natural gas usually contains more than 2% CO2, 4% N2, and 4 ppm hydrogen sulfide. The maximum nitrogen content in natural gas is required to be no higher than 1%. Excessive nitrogen will consume a lot of energy during the cooling process. Therefore, effectively removing nitrogen from low-quality natural gas is one of the most difficult energy challenges in the world.

[0003] However, there are not many studies on the separation of nitrogen and methane in existing technologies. SM Kuznicki's team reported a titanium silicon molecular sieve with adjustable pore size, using the "molecular gate" effect to separate molecules with a size of 4.0-3.0 Å, such as N2 / CH4; JS Chang's team reported a mesoporous metal organic framework material containing coordinated unsaturated Cr(III) sites for N2 / CH4 separation. S. Li's team prepared SAPO-34 membrane for N2 / CH4 separation, and the selectivity for 50 / 50 N2 / CH4 mixed gas reached 7.4 at room temperature. However, the separation of N2 / CH4 is far from ideal. Musselman et al. prepared MOF5@Matrimid, and Koros et al. prepared MOF5@PVAc mixed matrix membrane, using the different diffusion rates of nitrogen molecules and methane molecules in the material to achieve the separation of nitrogen and methane. Summary of the invention

[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to overcome the problem that the existing nitrogen / methane separation effect is not ideal, and a lithium-doped material with a simple preparation method and low cost is proposed, and the synthesized material can effectively separate nitrogen and methane, as well as its preparation method and application.

[0005] In order to solve the technical problem, the technical solution adopted by the present invention is:

[0006] In one aspect, the present invention provides a method for preparing a lithium-doped material, comprising a step of synthesizing Polymer 1 , a step of preparing naphthyl lithium, and a step of preparing Li@Polymer 1 ;

[0007] The preparation steps of Li@Polymer 1 include: mixing and stirring the dried Polymer 1 and a tetrahydrofuran solution of naphthyl lithium in a glove box, fully reacting, and draining the solvent under high vacuum conditions to obtain a solid powder of lithium-doped material; the synthesis steps of Polymer 1 include:

[0008] Naphthalene and anhydrous ferric chloride are placed in a three-necked flask, dimethoxymethane and 1,2-dichloroethane are added under nitrogen protection, the mixture is stirred evenly at room temperature, the temperature is then raised to 70-90°C, the mixture is stirred, after the reaction is completed, the mixture is filtered, washed, subjected to Soxhlet extraction with ethanol as solvent, and vacuum dried to obtain the polymer 1; specifically comprising: 1.28 g of naphthalene with a concentration of 10 mmol and 6.48 g of anhydrous ferric chloride with a concentration of 40 mmol are placed in a three-necked flask, 3.5 mL of dimethoxymethane with a concentration of 40 mmol and 20 mL of 1,2-dichloroethane are added under nitrogen protection, the mixture is stirred evenly at room temperature, the temperature is then raised to 80°C, the mixture is stirred for 36 h, after the reaction is completed, the mixture is filtered, the obtained solid is dispersed in 40 mL of 3 M hydrochloric acid, stirred for 1 h, suction filtered, subjected to Soxhlet extraction with ethanol as solvent for 36 h, and dried in a vacuum drying oven to obtain the polymer 1.

[0009] Preferably, the naphthyl lithium preparation step comprises: dissolving naphthalene in dry tetrahydrofuran in a glove box, adding lithium, and stirring to obtain the naphthyl lithium.

[0010] Preferably, the naphthyl lithium preparation step comprises: dissolving 0.512 g of naphthalene with a concentration of 4 mmol in 20 mL of dry tetrahydrofuran in a glove box, adding 0.0069 g of lithium with a concentration of 1 mmol, stirring for 2 h, the solution turns dark green, and the naphthyl lithium is obtained.

[0011] Preferably, the preparation step of the Li@Polymer 1 comprises: mixing and stirring 200 mg of dried Polymer 1 and 60 mL of tetrahydrofuran solution of naphthyl lithium in a glove box for 2-36 h to fully react, draining the solvent under high vacuum conditions, and storing the solid powder in a glove box with an argon environment to obtain the Li@Polymer 1; and regulating the concentration of lithium in the material by regulating the amount of the polymer.

[0012] Preferably, in the Li@Polymer 1 preparation step, draining the solvent under high vacuum conditions comprises: -2 -10 -4 Pa, temperature is 120℃, and pump dry for 12 h.

[0013] Another aspect of the present invention provides a lithium-doped material prepared by the method for preparing a lithium-doped material described in any of the above technical solutions.

[0014] The present invention also provides the use of the lithium-doped material described in the above technical solution in nitrogen / methane separation or CO2 / N2 separation.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention provides a method for preparing a lithium-doped material, which has the characteristics of being simple in preparation method and low in cost, and the synthesized material can effectively separate nitrogen and methane;

[0017] The present invention also provides an application of a lithium-doped material in nitrogen / methane separation. The lithium-doped material is based on chemical adsorption of nitrogen, that is, nitrogen molecules react chemically with active sites in the material to fix the nitrogen in the material, and the material has no adsorption capacity for methane. Based on this principle, nitrogen and methane are successfully separated. At the same time, the adsorption of nitrogen by the material is reversible, and nitrogen is released at high temperature, ensuring the recyclability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the adsorption curve of nitrogen by Li@Polymer 1 provided in Example 1 of the present invention;

[0019] Figure 2 is the nitrogen adsorption curve of Li@Polymer 1 after regeneration;

[0020] Figure 3 is the adsorption of carbon dioxide by Li@Polymer 1. DETAILED DESCRIPTION

[0021] The technical scheme in the specific embodiment of the present invention is described in detail and completely below. Obviously, the described embodiment is only a part of the specific implementation of the overall technical scheme of the present invention, rather than all implementations. Based on the overall concept of the present invention, all other embodiments obtained by ordinary technicians in this field fall within the scope of protection of the present invention.

[0022] In one aspect, the present invention provides a method for preparing a lithium-doped material, comprising a step of synthesizing Polymer 1 , a step of preparing naphthyl lithium, and a step of preparing Li@Polymer 1 ;

[0023] Among them, Polymer 1 can also be replaced by a naphthyl-containing polymer or other materials, such as the following polymer Polymer 2, which can also be used to prepare Li@Polymer 2 for the separation of nitrogen and methane:

[0024] The synthetic route of Polymer 2 in the synthetic step of Polymer 2 is:

[0025] The synthetic route of Polymer 2 in the synthetic step of Polymer 2 is: ; or the synthetic route of Polymer 1 is: ;

[0026] The naphthyl lithium synthesis route of the naphthyl lithium preparation step is: ;

[0027] The preparation steps of Li@Polymer 1 include: mixing and stirring the dried Polymer 1 and a tetrahydrofuran solution of naphthyl lithium in a glove box, allowing the mixture to react fully, and then draining the solvent under high vacuum conditions to obtain a solid powder of the lithium-doped material.

[0028] The preparation method is simple and low in cost, and the synthesized material can effectively separate nitrogen and methane.

[0029] In a preferred embodiment, the synthesis step of Polymer 1 includes: placing naphthalene and anhydrous ferric chloride in a three-necked flask, adding dimethoxymethane and 1,2-dichloroethane under nitrogen protection, stirring evenly at room temperature, then heating to 70-90°C, stirring, filtering after the reaction is completed, washing, performing Soxhlet extraction with ethanol as solvent, and vacuum drying to obtain Polymer 1. Specifically, 1.28 g of naphthalene with a concentration of 10 mmol and 6.48 g of anhydrous ferric chloride with a concentration of 40 mmol are placed in a three-necked flask, under nitrogen protection, adding 3.5 mL of dimethoxymethane with a concentration of 40 mmol and 20 mL of 1,2-dichloroethane, stirring evenly at room temperature, then heating to 80°C, stirring for 36 h, filtering after the reaction is completed, dispersing the obtained solid in 40 mL of 3 M hydrochloric acid, stirring for 1 h, suction filtering, performing Soxhlet extraction with ethanol as solvent for 36 h, and drying in a vacuum drying oven to obtain Polymer 1.

[0030] The preparation process of Polymer 2 includes:

[0031] Naphthalene (0.3 g, 2.5 mmol) was dissolved in 24 ml of chloroform. Anhydrous aluminum chloride (2.67 g, 15 mmol) was added under argon protection and stirred evenly at room temperature. The mixture was heated to 58 °C and stirred for 48 h. After the reaction was completed, it was filtered and repeatedly washed with ethanol and hydrochloric acid-deionized water (V:V = 2:1). Soxhlet extraction was performed with ethanol as solvent for 36 h and dried in a vacuum oven to obtain Polymer 2.

[0032] Regarding the above Polymer 1 and Polymer 2, it should be noted that, as shown in the above synthesis route, Polymer 1 is formed by naphthalene rings connected via methylene bridges. Because the material is insoluble, its molecular weight and molecular weight distribution cannot be tested. Polymer 2 is prepared based on the Scholl reaction. The naphthalene rings are directly connected to form a porous polymer. Because the material is insoluble, its molecular weight and molecular weight distribution cannot be tested. The specific surface area of ​​Polymer 1 and Polymer 2 measured by the specific surface area analyzer is about 900-1000 m 2 / g. Li@Polymer is difficult to characterize because of its unstable chemical properties and inactivation upon contact with air and water.

[0033] In a preferred embodiment, the preparation step of the naphthyl lithium includes: dissolving naphthalene in dry tetrahydrofuran in a glove box, adding lithium, stirring, and obtaining the naphthyl lithium. Specifically: dissolving 0.512 g of naphthalene with a concentration of 4 mmol in 20 mL of dry tetrahydrofuran in a glove box, adding 0.0069 g of lithium with a concentration of 1 mmol, stirring for 2 h, and the solution is dark green to obtain the naphthyl lithium.

[0034] In a preferred embodiment, the preparation step of Li@Polymer 1 includes: mixing 200 mg of dried Polymer 1 and 60 mL of tetrahydrofuran solution of naphthyl lithium in a glove box for 2-36 h to fully react, draining the solvent under high vacuum conditions, and storing the solid powder in a glove box in an argon environment to obtain the Li@Polymer 1; and regulating the concentration of lithium in the material by regulating the amount of the polymer. In a preferred embodiment, in the preparation step of Li@Polymer 1, draining the solvent under high vacuum conditions includes: -2 -10 -4 Pa, temperature is 120℃, and pump dry for 12 h.

[0035] Another aspect of the present invention provides a lithium-doped material prepared by the method for preparing a lithium-doped material according to any of the above technical solutions. The lithium-doped material can effectively separate nitrogen and methane.

[0036] The present invention also provides the application of the lithium-doped material described in the above technical solution in nitrogen / methane separation or CO2 / N2 separation. In a preferred embodiment, when the lithium-doped material is used for the separation of nitrogen and methane, the lithium-doped material adsorbs nitrogen on the lithium-doped material by chemical adsorption, thereby achieving the separation of nitrogen and methane. The lithium-doped material is based on the chemical adsorption of nitrogen, that is, the nitrogen molecules and the active sites in the material undergo a chemical reaction to fix the nitrogen in the material, and the material has no adsorption capacity for methane. Based on this principle, nitrogen and methane are successfully separated. At the same time, the adsorption of nitrogen by the material is reversible, and nitrogen is released at high temperature, ensuring the recyclability of the material.

[0037] Among them, nitrogen reacts with lithium in the material to form lithium nitride, which decomposes into nitrogen and lithium after heating. As shown in the equation:

[0038] At room temperature and 1 bar pressure, the adsorption of nitrogen by Li@Polymer1 is about 2 cm 3 / g (0.25 wt%). Treated at 300℃ for 2 hours. The second test showed an adsorption capacity of about 1.5 cm 3 / g. The nitrogen adsorption capacity did not decrease significantly. After further treatment at 300℃ for 2 hours, the nitrogen adsorption test of Li@Polymer1 showed no adsorption capacity ( Figure 3 ). The material will quench the activity of lithium when it comes into contact with air and water. Since the test and pretreatment are not carried out in situ, it is possible that the sample has deteriorated during the transfer process.

[0039] In the process of separating nitrogen and methane, the separation ability of this material is mainly evaluated by its nitrogen adsorption ability and the regeneration performance of the material. Nitrogen and lithium react to form lithium nitride. This reaction is reversible and nitrogen can be decomposed by heating to facilitate the recycling of the material. Nitrogen desorption can be achieved at 300°C.

[0040] In order to more clearly and in detail introduce the lithium-doped material, preparation method and application thereof provided by the embodiments of the present invention, a description will be given below in conjunction with specific embodiments.

[0041] Example 1

[0042] Synthesis of Polymer 1:

[0043] Naphthalene (1.28 g, 10 mmol) and anhydrous ferric chloride (6.48 g, 40 mmol) were placed in a three-necked flask. Under nitrogen protection, dimethoxymethane (3.5 mL, 40 mmol) and 20 mL of 1,2-dichloroethane were added and stirred evenly at room temperature. Then the temperature was raised to 80 °C and stirred for 36 h. After the reaction was completed, the solid was filtered and dispersed in 40 mL of hydrochloric acid (3 M), stirred for 1 h, and filtered. This step was repeated 3 times. Soxhlet extraction was performed with ethanol as the solvent for 36 h and dried in a vacuum oven to obtain Polymer 1. The specific surface area of ​​Polymer 1 was 1000 m 2 / g.

[0044] Preparation of lithium naphthyl:

[0045] In a glove box, naphthalene (0.512 g, 4 mmol) was dissolved in 20 mL of dry tetrahydrofuran, lithium (0.0069 g, 1 mmol) was added, and the mixture was stirred vigorously for 2 h. The solution turned dark green.

[0046] Preparation of Li@Polymer 1:

[0047] In a glove box, dry Polymer 1 (200 mg) and a tetrahydrofuran solution of naphthyl lithium (60 mL) were mixed and stirred for 36 h to allow the lithium and polymer to react fully. The solvent was then drained under high vacuum (10 -4 Pa, 120 °C, 12 h), the solid powder Li@Polymer 1 was kept in a glove box (argon environment) for testing.

[0048] Performance Testing

[0049] like Figure 1 As shown in Figure 2, at room temperature and 1 bar pressure, the adsorption of nitrogen by Li@Polymer 1 reaches 2 cm 3 / g. The sample after nitrogen adsorption was vacuum treated at 100-300℃ for 2 h; at room temperature and 1 bar pressure, the adsorption of nitrogen reached 1.5 cm 3 / g.

[0050] like Figure 2 As shown, Li@Polymer1 has an adsorption capacity of about 2 cm2 for nitrogen at room temperature and 1 bar pressure. 3 / g (0.25wt%). Treated at 300℃ for 2 hours. The second test showed an adsorption capacity of about 1.5 cm 3 / g. The nitrogen adsorption capacity did not decrease significantly. After being treated at 300℃ for another 2 hours, the nitrogen adsorption test of Li@Polymer1 showed no adsorption capacity. The activity of lithium will be quenched when the material encounters air and water. Since the test and pretreatment are not carried out in situ, it is possible that the sample deteriorated during the transfer process.

[0051] In the process of separating nitrogen and methane, the separation ability of this material is mainly evaluated by its nitrogen adsorption ability and the regeneration performance of the material. Nitrogen and lithium react to form lithium nitride. This reaction is reversible and nitrogen can be decomposed by heating to facilitate the recycling of the material. Nitrogen desorption can be achieved at 300°C.

[0052] like Figure 3 As shown, at room temperature and 1 bar pressure, the adsorption of carbon dioxide reaches 82 cm 3 The sample was heated at 300℃ for 2 hours and tested for the second time. At room temperature and 1 bar pressure, the adsorption of carbon dioxide reached 20 cm 3 / g. After nitrogen adsorption, it can be desorbed, but after carbon dioxide adsorption, it is difficult to desorb at 300°C. Therefore, it can be used to separate carbon dioxide and nitrogen; this material has no adsorption to methane, so it can be used to separate carbon dioxide and methane. However, it cannot be recycled.

Claims

1. A method for preparing a lithium-doped material, characterized in that: The method includes a step of synthesizing Polymer 1, a step of preparing naphthyl lithium, and a step of preparing Li@Polymer 1; The preparation steps of Li@Polymer 1 include: mixing and stirring dried Polymer 1 and a tetrahydrofuran solution of lithium naphthyl in a glove box, allowing the mixture to react fully, and then draining the solvent under high vacuum conditions to obtain a solid powder of the lithium-doped material; The Polymer 1 synthesis steps include: Naphthalene and anhydrous ferric chloride are placed in a three-necked flask, and dimethoxymethane and 1,2-dichloroethane are added under nitrogen protection, and the mixture is stirred evenly at room temperature, and then the temperature is raised to 70-90° C. and stirred. After the reaction is completed, the mixture is filtered, washed, and subjected to Soxhlet extraction with ethanol as a solvent, and vacuum dried to obtain the polymer 1; Specifically include: 1.28 g of naphthalene (10 mmol) and 6.48 g of anhydrous ferric chloride (40 mmol) were placed in a three-necked flask. Under nitrogen protection, 3.5 mL of dimethoxymethane (40 mmol) and 20 mL of 1,2-dichloroethane were added. The mixture was stirred evenly at room temperature, then heated to 80° C. and stirred for 36 h. After the reaction was completed, the mixture was filtered and the obtained solid was dispersed in 40 mL of 3 M hydrochloric acid. The mixture was stirred for 1 h, filtered, and Soxhlet extracted with ethanol for 36 h. The mixture was dried in a vacuum drying oven to obtain Polymer 1. The preparation steps of the naphthyl lithium include: dissolving naphthalene in dry tetrahydrofuran in a glove box, adding lithium, and stirring to obtain the naphthyl lithium.

2. The method for preparing a lithium-doped material according to claim 1, wherein: The preparation steps of the naphthyl lithium include: dissolving 0.512 g of naphthalene with a concentration of 4 mmol in 20 mL of dry tetrahydrofuran in a glove box, adding 0.0069 g of lithium with a concentration of 1 mmol, and stirring for 2 hours. The solution turns dark green to obtain the naphthyl lithium.

3. The method for preparing a lithium-doped material according to claim 1, wherein: The preparation steps of the Li@Polymer 1 include: mixing 200 mg of dried Polymer 1 and 60 mL of a tetrahydrofuran solution of naphthyl lithium in a glove box and stirring for 2-36 hours to fully react, draining the solvent under high vacuum conditions, and storing the solid powder in an argon environment in a glove box to obtain the Li@Polymer 1; and regulating the lithium concentration in the material by adjusting the amount of the polymer.

4. The method for preparing a lithium-doped material according to claim 1, wherein: In the preparation step of Li@Polymer 1, the step of extracting the solvent under high vacuum conditions comprises: -2 -10 -4 Pa, temperature is 120℃, and pump dry for 12 h.

5. The lithium-doped material prepared according to the method for preparing a lithium-doped material according to any one of claims 1 to 4.

6. Use of the lithium-doped material according to claim 5 in nitrogen / methane separation or CO2 / N2 separation.